Polycarbonate resin, curable resin composition, and cured material

By combining polycarbonate resin with epoxy resin with specific structural units, the problem of insufficient dielectric performance and thermal stability in high-frequency applications of existing materials is solved, and polymer materials with low dielectric constant and low dielectric loss tangent are achieved, suitable for high-frequency electrical and thermal materials.

JP2025017386APending Publication Date: 2025-02-06TEIJIN LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023120359
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

It is difficult for existing polymer materials to have low dielectric constant, low dielectric loss tangent and good thermal stability in high-frequency applications, and the existing methods of adding polycarbonate resins have problems of incompatibility or increasing dielectric loss tangent.

Method used

Polycarbonate resins with specific structural units, containing more than 70 mol% of specific structural units, and combined with epoxy resin to make a curable resin composition. By controlling molecular weight and dielectric properties, low dielectric constant and low dielectric loss tangent are achieved.

Benefits of technology

It achieves a polymer material with low dielectric constant and low dielectric loss tangent, with excellent thermal stability and transparency, and is suitable for high-frequency electrical and thermal materials, especially insulating layers of printed circuit boards and semiconductor encapsulators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025017386000001
    Figure 2025017386000001
  • Figure 2025017386000002
    Figure 2025017386000002
  • Figure 2025017386000003
    Figure 2025017386000003
Patent Text Reader

Abstract

To provide: a polycarbonate resin which shows a low dielectric constant and a low dielectric loss tangent and has excellent heat resistance; a curable resin composition which comprises the polycarbonate resin, shows a low dielectric constant and a low dielectric loss tangent and has excellent transparency and good dimension stability; and a cured material obtained by curing the curable resin composition.SOLUTION: A polycarbonate resin comprises a structural unit (A) represented by the following formula (1), where the ratio of the structural unit (A) based on all structural units is 70 mol% or more and the following (a) and (b) are satisfied: (a) the polycarbonate resin has a weight average molecular weight, as measured by gel permeation chromatography, in the range of 5,000 to 15,000; and (b) the polycarbonate resin has, as measured according to a cavity resonator perturbation method at 10 GHz, a relative dielectric constant in the range of 2.30-2.70 and a dielectric loss tangent in the range of 0.0001-0.0030.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polycarbonate resin that exhibits a low dielectric constant, a low dielectric dissipation factor, and excellent heat resistance. The present invention also relates to a curable resin composition that uses the polycarbonate resin as a curing agent and exhibits a low dielectric constant, a low dielectric dissipation factor, excellent transparency, and good dimensional stability, and a cured product obtained by curing the curable resin composition. [Background technology]

[0002] Mobile wireless communication services, such as mobile phones, which were used for voice calls, are now being used as a means of accessing the Internet due to the development of communication and information processing technology. In addition, communication between people and between machines and things is about to begin in earnest for the purpose of control, sensing, and monitoring. In order to deal with the significant increase in network traffic, the next-generation wireless communication standard 5G system (hereinafter referred to as 5G) has begun operation. While previous communication systems (e.g., 4G LTE) have used low frequency bands of 2.5 GHz or less, 5G will use high frequency bands of 6 GHz or more. Therefore, future 5G-compatible devices will be required to be compatible with high-frequency signals. For example, low transmission loss can be mentioned as a high-frequency countermeasure for printed circuit boards (hereinafter referred to as PCBs). The transmission loss here refers to the conductor loss originating from the conductors (e.g., copper circuits) that make up the PCB, and the dielectric loss originating from the dielectric (insulating material around the circuit). One of the countermeasures for the former is to smooth the conductor surface, but it can be said that this is not expected to have a significant improvement effect. Specifically, since dielectric loss depends on the frequency of the current and the dielectric constant and dielectric dissipation factor of the insulating material around the circuit, there is a demand for low-dielectric insulating materials.In addition, there is a demand for insulating materials that have the same workability and physical properties (e.g., heat resistance, adhesiveness, insulating properties, etc.) as conventional circuit board materials.

[0003] PCBs are divided into package substrates that are placed directly under chips such as mobile processors, rigid substrates for main boards on which the package substrates are mounted, and flexible printed circuit boards used as LCD drivers, camera modules, and film antennas. Thermosetting resins are used for these insulating materials, and the resin composition is composed of (i) thermosetting and crosslinking components such as epoxy resins and maleimide resins, (ii) filler components to impart flame retardancy, heat resistance, and low linear expansion coefficient, and (iii) polymers used to improve flexibility and adhesion. Polymers used as insulating materials for PCBs generally require heat resistance, adhesion, processability, flexibility, and compatibility. Carboxyl-modified acrylonitrile-butadiene copolymer rubber, acrylic polymers, urethane polymers, etc. have been used for conventional PCB polymers. However, there are no materials that have the low dielectric properties required for high-frequency applications, and new materials are currently required.

[0004] Therefore, a curable resin composition containing a predetermined amount of polycarbonate resin has been studied for the purpose of reducing the dielectric constant and improving flexibility and adhesion. For example, Patent Documents 1 and 2 disclose a resin composition containing an epoxy resin, a curing agent, a polycarbonate resin, and an inorganic filler. However, even if a polycarbonate resin is added to a curable resin composition, the composition becomes incompatible during curing, so that the effect of adding the polycarbonate resin is not easily expressed and the amount of addition is limited. In addition, Patent Documents 3, 4, and 5 disclose a method of adding an allyl group-containing aliphatic polycarbonate resin to a curable resin composition. However, although the compatibility of the curable resin composition is improved by including an allyl group, the dielectric loss tangent is increased by copolymerizing an aliphatic diol. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-35056 A [Patent Document 2] JP 2022-133793 A [Patent Document 3] JP 2019-89965 A [Patent Document 4] JP 2019-89966 A [Patent Document 5] JP 2019-89967 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a polycarbonate resin that exhibits a low dielectric constant, a low dielectric dissipation factor, and excellent heat resistance. Another object of the present invention is to provide a curable resin composition that contains the polycarbonate resin, exhibits a low dielectric constant, a low dielectric dissipation factor, is excellent in transparency, and has good dimensional stability, and a cured product obtained by curing the curable resin composition. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have surprisingly found that the above object can be achieved by using a polycarbonate resin containing a specific structural unit. Based on this finding, the present inventors have furthered their investigations and have completed the present invention.

[0008] That is, according to the present invention, the following (Configuration 1) to (Configuration 8) are provided. (Configuration 1) A polycarbonate resin comprising a structural unit (A) represented by the following formula (1), the proportion of the structural unit (A) in all structural units being 70 mol % or more, and satisfying the following (a) and (b): (a) the weight average molecular weight of the polycarbonate resin measured by gel permeation chromatography is in the range of 5,000 to 15,000; (b) The relative dielectric constant of polycarbonate resin at a frequency of 10 GHz measured in accordance with a cavity resonator perturbation method is in the range of 2.30 to 2.70, and the dielectric tangent is in the range of 0.0001 to 0.0030;

[0009] [ka] (In formula (1), R1 and R2 each independently represent a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms; R3 and R4 each independently represent a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms; and X represents a single bond, a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, a substituted or unsubstituted alkylidene group having 2 to 20 carbon atoms, a substituted or unsubstituted sulfur atom, or an oxygen atom.)

[0010] (Configuration 2) The polycarbonate resin according to embodiment 1, wherein X in the formula (1) is at least one group selected from the group consisting of the following formula (2):

[0011] [ka] (R5 and R6 each independently represent a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, and Z represents a substituted or unsubstituted alkylene group having 4 to 12 carbon atoms.)

[0012] (Configuration 3) 3. The polycarbonate resin according to claim 1, wherein the proportion of the structural unit (A) in all structural units of the polycarbonate resin is 80 mol % or more. (Configuration 4) The polycarbonate resin according to any one of configurations 1 to 3, wherein R1 and R2 in the formula (1) are each at least one group selected from the group consisting of a methyl group, an isopropyl group, a tertiary butyl group, a cyclohexyl group, and a phenyl group, and R3 and R4 are each a hydrogen atom or a methyl group. (Configuration 5) The polycarbonate resin according to any one of configurations 1 to 4, which is a polycarbonate resin produced by an interfacial polycondensation method between a dihydroxy compound which derives the structural unit (A) represented by the formula (1) and carbonyl chloride. (Configuration 6) A curable resin composition comprising the polycarbonate resin according to any one of configurations 1 to 5 and an epoxy resin. (Configuration 7) 7. The curable resin composition according to claim 6, which is a curable resin composition for forming an insulating layer of a printed wiring board. (Configuration 8) A cured product obtained by curing the curable resin composition according to configuration 6. Effect of the Invention

[0013] The polycarbonate resin of the present invention exhibits a low dielectric constant, a low dielectric loss tangent, and is excellent in heat resistance. In addition, a curable resin composition using the polycarbonate resin as a curing agent and a cured product obtained by curing the curable resin composition exhibit a low dielectric constant, a low dielectric loss tangent, excellent transparency, and good dimensional stability. Such a curable resin composition and cured product are extremely useful as a highly functional polymer material, and as an electrically and thermally excellent material, they can be used in a wide range of applications, such as an interlayer insulating layer for printed wiring boards, a semiconductor sealant, an electrical insulating material, a resin for copper-clad laminates, a resist, a resin for sealing electronic components, a resin for color filters of liquid crystals, a paint, various coating agents, adhesives, build-up laminate materials, fiber-reinforced plastic (FRP) materials, etc. Therefore, the industrial effects that they achieve are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Polycarbonate resin> The polycarbonate resin of the present invention contains a structural unit (A) represented by the following formula (1).

[0015] [ka]

[0016] In formula (1), R1 and R2 each independently represent a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, and R3 and R4 each independently represent a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms.

[0017] Examples of the substituted or unsubstituted alkyl group having 1 to 6 carbon atoms for R1 and R2 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, a sec-pentyl group, and an n-hexyl group. Examples of the substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms include a cyclohexyl group, a cycloheptyl group, and a cyclooctyl group. Examples of the substituted or unsubstituted aryl group having 6 to 20 carbon atoms include a phenyl group, a benzyl group, a tolyl group, a 4-methylphenyl group, and a naphthyl group.

[0018] Among these, R1 and R2 are preferably a methyl group, an isopropyl group, a tert-butyl group, a cyclohexyl group, or a phenyl group, more preferably a methyl group or a tert-butyl group, and particularly preferably a methyl group.

[0019] Examples of the substituted or unsubstituted alkyl group having 1 to 6 carbon atoms for R3 and R4 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, a sec-pentyl group, and an n-hexyl group. Examples of the substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms include a cyclohexyl group, a cycloheptyl group, and a cyclooctyl group. Examples of the substituted or unsubstituted aryl group having 6 to 20 carbon atoms include a phenyl group, a benzyl group, a tolyl group, a 4-methylphenyl group, and a naphthyl group.

[0020] Among these, R3 and R4 are preferably a hydrogen atom, a methyl group, an ethyl group, an n-propyl group, or a 4-methylphenyl group, and particularly preferably a hydrogen atom or a methyl group. Here, the bonding positions of R1, R2, R3, and R4 in formula (1) are any positions selected from the 2-position, 3-position, 5-position, and 6-position relative to X on each phenyl ring, and preferably the 3-position and the 5-position.

[0021] In formula (1), X represents a single bond, a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, a substituted or unsubstituted alkylidene group having 2 to 20 carbon atoms, a substituted or unsubstituted sulfur atom, or an oxygen atom. Examples of the substituted or unsubstituted sulfur atom include -S- and -SO2-. The substituted or unsubstituted alkylene group having 1 to 20 carbon atoms or the substituted or unsubstituted alkylidene group is preferably at least one group selected from the group consisting of the following formula (2).

[0022] [ka] (R5 and R6 each independently represent a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, and Z represents a substituted or unsubstituted alkylene group having 4 to 12 carbon atoms.)

[0023] Examples of the substituted or unsubstituted alkyl group having 1 to 20 carbon atoms for R5 and R6 include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, a sec-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, etc. Examples of the substituted or unsubstituted aryl group having 6 to 20 carbon atoms include a phenyl group, a benzyl group, a tolyl group, a 4-methylphenyl group, a naphthyl group, etc. Among these, R5 and R6 are preferably a methyl group, an ethyl group, an n-propyl group or a 4-methylphenyl group, and more preferably a methyl group.

[0024] In formula (1), Z is bonded to the carbon that bonds the two phenyl groups to form a substituted or unsubstituted divalent carbocyclic ring. Examples of the divalent carbocyclic ring include cycloalkylidene groups (preferably having 5 to 8 carbon atoms) such as a cyclopentylidene group, a cyclohexylidene group, a cycloheptylidene group, a cyclododecylidene group, or an adamantylidene group, and examples of the substituted carbocyclic ring include those having a methyl or ethyl substituent. Among these, a cyclohexylidene group and a methyl-substituted cyclohexylidene group are preferred.

[0025] The polycarbonate resin of the present invention must contain the structural unit (A) represented by formula (1). The proportion of the structural unit (A) in the total structural units of the polycarbonate resin is 70 mol% or more, preferably 80 mol% or more, more preferably 90 mol% or more, and even more preferably 95 mol% or more. If the structural unit (A) of formula (1) is less than 70 mol%, the dielectric properties are inferior, which is not preferred.

[0026] The polycarbonate resin used in the present invention can be obtained by reacting a dihydroxy compound with a carbonyl compound. Examples of the reaction method include an interfacial polycondensation method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound. In the case of interfacial polycondensation, a terminal terminator of a monohydric phenol is usually used. In addition, it may be a branched polycarbonate obtained by polymerizing a trifunctional component, or a copolymerized polycarbonate obtained by copolymerizing an aliphatic dicarboxylic acid, an aromatic dicarboxylic acid, and a vinyl monomer.

[0027] The polycarbonate resin of the present invention is produced by a reaction means known per se for producing a normal polycarbonate resin, for example, a method of reacting a dihydroxy compound with a carbonyl compound such as phosgene or a carbonic acid diester. Next, the basic means for these production methods will be briefly described.

[0028] In a reaction using, for example, carbonyl chloride (phosgene) as a carbonyl compound, the reaction is usually carried out in the presence of an acid binder and a solvent. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, or an amine compound such as pyridine, is used. As the solvent, for example, a halogenated hydrocarbon such as methylene chloride or chlorobenzene is used. In addition, a catalyst such as a tertiary amine or a quaternary ammonium salt can be used to promote the reaction. In this case, the reaction temperature is usually 0 to 40°C, and the reaction time is several minutes to 5 hours.

[0029] The polycarbonate resin of the present invention preferably contains a terminal structure (B) derived from a monohydroxy compound represented by the following formula (3), which is used as a terminal terminator in the polymerization reaction.

[0030] [ka]

[0031] In formula (3), R7 is a hydrogen atom, a linear or branched alkyl group having 1 to 9 carbon atoms, a linear or branched alkoxy group having 1 to 10 carbon atoms, or a linear or branched phenyl-substituted alkyl group having 1 to 20 carbon atoms, and R8 is an allyl group having 3 to 20 carbon atoms. Here, the bonding position of R8 in formula (3) is any position selected with respect to the OH group on each phenyl ring, and is preferably the ortho position.

[0032] Specific examples of the monohydroxy compound include 2-allylphenol, chavicol, eugenol, etc. These may be used alone or in combination of two or more kinds.

[0033] The terminal structures derived from these monohydroxy compounds preferably account for 10 mol % or more, more preferably 30 mol % or more, and even more preferably 50 mol % or more, of all terminal structures constituting the obtained polycarbonate resin.

[0034] The polycarbonate resin of the present invention can be used in combination with a commonly used monofunctional phenol as a terminal terminator. In particular, in the case of a reaction using phosgene as a carbonate precursor, a monofunctional phenol is commonly used as a terminal terminator for molecular weight control, and the obtained polycarbonate resin has terminals blocked by groups based on a monofunctional phenol, and therefore has superior thermal stability compared to those not blocked.

[0035] Such monofunctional phenols may be any that can be used as terminal terminators for polycarbonate resins, and are generally phenol or lower alkyl-substituted phenols, and can include monofunctional phenols represented by the following formula (4).

[0036] [ka]

[0037] In formula (4), A is a linear or branched alkyl group or an arylalkyl group having 1 to 9 carbon atoms, and r is an integer of 1 to 5, preferably 1 to 3.

[0038] Specific examples of the monofunctional phenols include phenol, p-tert-butylphenol, p-cumylphenol, and isooctylphenol. As other monofunctional phenols, phenols or benzoic acid chlorides having a long-chain alkyl group or an aliphatic ester group as a substituent, or long-chain alkyl carboxylic acid chlorides can be used, and when these are used to block the ends of a polycarbonate polymer, they not only function as end terminators or molecular weight regulators, but also improve the melt fluidity of the resin, making molding easier, and have the effect of lowering the physical properties of the molded product, particularly the water absorption rate of the resin, and also have the effect of reducing the birefringence of the molded product, so they are preferably used. Among them, phenols having a long-chain alkyl group as a substituent, represented by the following formula (5) and the following formula (6), are preferably used.

[0039] [ka] [ka]

[0040] In formula (6), Z is -RO-, -R-CO-O- or -RO-CO-, where R is a single bond or a divalent aliphatic hydrocarbon group having 1 to 10 carbon atoms, preferably 1 to 5 carbon atoms, and n is an integer of 10 to 50.

[0041] As the substituted phenols of the formula (5), those in which n is 10 to 30, particularly 10 to 26, are preferred. Specific examples thereof include decylphenol, dodecylphenol, tetradecylphenol, hexadecylphenol, octadecylphenol, eicosylphenol, docosylphenol, and triacontylphenol.

[0042] As the substituted phenol of the formula (6), a compound in which Z is -R-CO-O- and R is a single bond is suitable, and one in which n is 10 to 30, particularly preferably 10 to 26, is preferred. Specific examples thereof include decyl hydroxybenzoate, dodecyl hydroxybenzoate, tetradecyl hydroxybenzoate, hexadecyl hydroxybenzoate, eicosyl hydroxybenzoate, docosyl hydroxybenzoate, and tricontyl hydroxybenzoate.

[0043] These monofunctional phenols can be used in an amount of 90 mol % or less based on the total terminals of the resulting polycarbonate resin. The monofunctional phenols may be used alone or in combination of two or more kinds.

[0044] In addition, the terminal OH group equivalent to the total structural units of the polycarbonate resin is preferably 50 ppm or more, more preferably 80 ppm or more, and even more preferably 100 ppm or more. If it is above the lower limit, the effect as a curing agent is enhanced. In addition, the terminal OH group equivalent is preferably 1,000 ppm or less, more preferably 700 ppm or less, and even more preferably 500 ppm or less. If it is below the upper limit, the thermal stability is excellent.

[0045] In the polycarbonate resin of the present invention, the proportion of structural units (A) in all structural units is 70 mol % or more, but structural units (C) derived from other dihydroxy components or diol components may be contained within a range that does not impair the effects of the present invention, for example, in an amount of 30 mol % or less, preferably 20 mol % or less, and more preferably 10 mol % or less of all structural units.

[0046] Examples of such dihydroxy components include hydroquinone, resorcinol, 4,4'-biphenol, 4,4'-bis(2,6-dimethyl)diphenol, 2,4'-dihydroxydiphenylmethane, bis(2-hydroxyphenyl)methane, bis(4-hydroxyphenyl)methane, bis(4-hydroxyphenyl)cyclohexylmethane, bis(4-hydroxyphenyl)diphenylmethane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxy-2-chlorophenyl)ethane, 2,2-bis(4-hydroxyphenyl)-1-phenylpropane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(4-hydroxyphenyl)diphenylmethane ... Examples of such hydroxyphenyl compounds include 4,4'-(p-phenylenediisopropylidene)diphenol, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-dihydroxydiphenyl sulfone, 2,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfoxide, and 4,4'-dihydroxydiphenyl sulfide. These compounds may be used alone or in combination of two or more.

[0047] In addition, examples of diol components include isosorbide:1,4:3,6-dianhydro-D-sorbitol, tricyclodecane dimethanol (TCDDM), 4,8-bis(hydroxymethyl)tricyclodecane, tetramethylcyclobutanediol (TMCBD), 2,2,4,4-tetramethylcyclobutane-1,3-diol, mixed isomers, cis / trans-1,4-cyclohexanedimethanol (CHDM), cis / trans-1,4-bis(hydroxymethyl)cyclohexane, cyclohex-1,4-yl enediol, and the like. Methanol, trans-1,4-cyclohexanedimethanol (tCHDM), trans-1,4-bis(hydroxymethyl)cyclohexane, cis-1,4-cyclohexanedimethanol (cCHDM), cis-1,4-bis(hydroxymethyl)cyclohexane, cis-1,2-cyclohexanedimethanol, 1,1'-bi(cyclohexyl)-4,4'-diol, spiroglycol, dicyclohexyl-4,4'-diol, 4,4'-dihydroxybicyclohexyl, and poly(ethylene glycol).

[0048] (Properties of polycarbonate resin) The number average molecular weight and weight average molecular weight of the polycarbonate resin of the present invention can be measured by gel permeation chromatography using standard polystyrene as a reference. The weight average molecular weight of the polycarbonate resin of the present invention is in the range of 5,000 to 15,000, preferably in the range of 6,000 to 14,000, more preferably in the range of 7,000 to 12,500, and further preferably in the range of 8,000 to 11,000. If it is within this range, the compatibility with the epoxy resin curing agent is good, and the strength of the resin composition after curing is improved.

[0049] The glass transition temperature (Tg) of the polycarbonate resin of the present invention is preferably in the range of 100 to 150°C, more preferably 110 to 140°C, and further preferably 115 to 135°C. Tg within the above range is preferable since it has excellent heat resistance and processability. The glass transition temperature (Tg) is measured using a 2910-type DSC manufactured by TA Instruments Japan Co., Ltd. at a heating rate of 20°C / min.

[0050] The polycarbonate resin used in the present invention has a relative dielectric constant at a frequency of 10 GHz measured by a perturbation method using a cavity resonator in the range of 2.30 to 2.70, preferably in the range of 2.40 to 2.66. Also, the dielectric loss tangent at a frequency of 10 GHz measured by the same method is in the range of 0.0001 to 0.0030, preferably in the range of 0.0005 to 0.0025. If the relative dielectric constant and the dielectric loss tangent are within the above ranges, the dielectric loss of the insulating material is reduced, which is preferable.

[0051] (Curable resin composition and cured product) The polycarbonate resin used in the present invention can be used as a curing agent for curing an epoxy resin. The epoxy resin can be cured by heating. Furthermore, a cured product obtained by curing an epoxy resin with the polycarbonate resin of the present invention exhibits a high glass transition temperature, a high thermal decomposition temperature, and a low coefficient of linear thermal expansion due to the use of the epoxy resin.

[0052] The curable resin composition of the present invention contains the polycarbonate resin of the present invention. The polycarbonate resin has excellent impact resistance and therefore excellent mechanical strength, and therefore exhibits the effect of increasing the toughness of the cured product.

[0053] The content of the polycarbonate resin component is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, based on 100% by mass of the resin component of the curable resin composition. The upper limit is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less. By setting the content of the polycarbonate resin component within the above range, the toughness of the cured product can be improved.

[0054] In addition, since the polycarbonate resin of the present invention is used, the cured product obtained from the curable resin composition of the present invention has a lower dielectric constant and a lower dielectric tangent than a cured product obtained by curing an epoxy resin with a phenol novolac resin.

[0055] Furthermore, the polycarbonate resin of the present invention has excellent solubility in solvents that are generally used to dissolve epoxy compounds, and therefore a resin varnish in which both the polycarbonate resin of the present invention and the epoxy resin are dissolved in a solvent can be obtained. The solvent is generally a polar one such as methyl ethyl ketone.

[0056] The use of the curable resin composition and the cured product of the present invention is not particularly limited. For example, it may be the same as the use of known thermosetting molding materials, such as sealing materials, film materials, laminate materials, etc. More specific examples of the use include interlayer insulating layers of printed wiring boards, semiconductor sealing materials, sealing resin materials for electronic components, electrical insulating materials, resin materials for copper-clad laminates, build-up laminate materials, resist materials, resin materials for liquid crystal color filters, paints, various coating agents, adhesives, fiber-reinforced plastic (FRP) materials, etc.

[0057] (Dielectric constant, dielectric tangent) The curable resin composition of the present invention has a relative dielectric constant at a frequency of 10 GHz measured by a perturbation method using a cavity resonator, preferably in the range of 2.60 to 2.90, more preferably in the range of 2.70 to 2.85. Also, the dielectric loss tangent at a frequency of 10 GHz measured by the same method is preferably in the range of 0.005 to 0.025, more preferably in the range of 0.010 to 0.023. If the relative dielectric constant and the dielectric loss tangent are within the above ranges, the dielectric loss of the insulating material is reduced, which is preferable.

[0058] (Coefficient of linear expansion: CTE) The coefficient of linear expansion (CTE) of the curable resin composition in the present invention is preferably in the range of 40 to 65 ppm / °C, more preferably 45 to 62 ppm / °C, and further preferably 50 to 60 ppm / °C. When the CTE is within the above range, dimensional change due to heat is small, which is preferable. The coefficient of linear expansion (CTE) is measured at 30°C at a heating rate of 2°C / min using a linear expansion coefficient measuring device "TMA4000SE" manufactured by NETZSCH.

[0059] <Epoxy resin> The curable resin composition of the present invention can contain the polycarbonate resin of the present invention and the epoxy resin. The polycarbonate resin of the present invention has a phenolic hydroxyl group, so it can also be used as a curing agent (epoxy resin curing agent) for curing the epoxy resin. The epoxy resin can be cured by heating.

[0060] When an epoxy resin is cured using the polycarbonate resin of the present invention, it is believed that the curing occurs through the following reactions (1) and (2). (1) Reaction of epoxy groups with hydroxyl groups (2) Reaction between epoxy groups

[0061] Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, etc. The epoxy resins may be used alone or in combination of two or more.

[0062] <Solvent> The solvent is not particularly limited as long as it dissolves the components contained in the curable resin composition of the present invention (the polycarbonate resin of the present invention, the epoxy resin, and other epoxy curing agents and curing accelerators, etc., as necessary). Typically, a polar solvent is used as the solvent. Examples of the polar solvent include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ketone, methyl propyl ketone, methyl amyl ketone, isophorone, diisobutyl ketone, diacetone alcohol, and cyclohexanone, N,N-dimethylformamide, N-methyl-2-pyrrolidone, methanol, ethanol, butanol, ethyl acetate, butyl acetate, methyl cellosolve, ethyl diglycol acetate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and tetrahydrofuran. Any one of these solvents may be used alone, or two or more may be used in combination. Among the above, ketone-based solvents are preferred, and methyl ethyl ketone is more preferred.

[0063] <Curing reaction catalyst> Examples of the curing reaction catalyst (curing accelerator) include imidazole compounds, phosphorus compounds, tertiary amines, organic acid metal salts, Lewis acids, and amine complex salts. Examples of the imidazole compound include 2-ethyl-4-methylimidazole, 2-methylimidazole, 2-ethylimidazole, 2,4-dimethylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 1-vinyl-2-methylimidazole, 1-propyl-2-methylimidazole, 2-isopropylimidazole, 1-cyanomethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, and 1-cyanoethyl-2-phenylimidazole. For example, phosphorus compounds include triphenylphosphine, tris-2,6-dimethoxyphenylphosphine, tri-p-tolylphosphine, triphenyl phosphite, etc. Tertiary amines include 2-dimethylaminomethylphenol, benzyldimethylamine, α-methylbenzyldimethylamine, 1,8-diazabicyclo[5.4.0]undecene-7, etc.

[0064] When the curable resin composition contains an epoxy resin, an imidazole compound is preferably used as the curing reaction catalyst.

[0065] <Inorganic filler> The curable resin composition of the present invention may contain an inorganic filler. The inorganic filler can reduce the linear expansion coefficient of the cured product of the curable resin composition.

[0066] The material of the inorganic filler is not particularly limited as long as it is an inorganic compound, and examples thereof include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium titanate zirconate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. As the silica, spherical silica is preferable. The inorganic filler may be used alone or in combination of two or more.

[0067] The average particle size of the inorganic filler is usually 5 μm or less, preferably 2.5 μm or less, more preferably 1.5 μm or less, and even more preferably 1 μm or less. The lower limit of the average particle size is not particularly limited, but may be 1 nm (0.001 μm) or more, 5 nm or more, or 10 nm or more, etc. The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory.

[0068] The inorganic filler is preferably treated with a surface treatment agent, more preferably with one or more surface treatment agents such as a fluorine-containing silane coupling agent, an aminosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a silane coupling agent, an alkoxysilane compound, an organosilazane compound, a titanate coupling agent, etc., and even more preferably with an aminosilane silane coupling agent. The surface treatment agent preferably has a functional group that reacts with other components, such as a resin, such as an epoxy group, an amino group, or a mercapto group, and more preferably the functional group is bonded to the terminal group.

[0069] The content of the inorganic filler component is preferably 45 parts by weight or more, more preferably 50 parts by weight or more, and even more preferably 60 parts by weight or more, based on 100 parts by weight of the nonvolatile content in the curable resin composition, from the viewpoint of reducing the average linear expansion coefficient of the cured product obtained by curing the curable resin composition and from the viewpoint of improving the dielectric performance. The upper limit is not particularly limited, but is preferably 85 parts by weight or less, more preferably 80 parts by weight or less, and even more preferably 75 parts by weight or less.

[0070] <Flame retardants> The curable resin composition of the present invention may contain a flame retardant. Examples of the flame retardant include phosphazene compounds, organic phosphorus flame retardants, organic nitrogen-containing phosphorus compounds, nitrogen compounds, silicone flame retardants, metal hydroxides, etc. The flame retardants may be used alone or in combination of two or more.

[0071] When the curable resin composition contains a flame retardant, the content of the flame retardant is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and even more preferably 0.7 parts by weight or more, based on 100 parts by weight of the non-volatile content in the curable resin composition. This allows the curable resin composition and its cured product to have significant flame retardancy. The upper limit is preferably 5 parts by weight or less, more preferably 4 parts by weight or less, and even more preferably 3 parts by weight or less.

[0072] <Optional Additives> The curable resin composition of the present invention may contain other additives as necessary. Examples of such other additives include other thermoplastic resins, organic fillers, organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds, and resin additives such as thickeners, defoamers, leveling agents, adhesion promoters, and colorants.

[0073] Examples of the thermoplastic resin include phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyimide resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polyetheretherketone resin, polyester resin, etc. However, the thermoplastic resin mentioned here does not include the polycarbonate resin of the present invention.

[0074] As the organic filler, any organic filler that can be used when forming an insulating layer of a printed wiring board may be used, and examples thereof include rubber particles, polyamide fine particles, silicone particles, and the like. EXAMPLES

[0075] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples and comparative examples, the methods for measuring the various properties are as follows.

[0076] (Polymer Evaluation) (1) Weight average molecular weight (Mw) The obtained polycarbonate resin was used as a measurement sample, and the weight average molecular weight Mw was measured by gel permeation chromatography (GPC) and calculated by the polystyrene conversion method. A calibration curve was created using standard polystyrenes with known molecular weights (12 types from Tosoh PS Oligomer Kit A-500 to F-128). The measurement was performed using Tosoh's "HLC-8220GPC" and three columns, Tosoh's "TSK-gel SuperHZ4000 / 3000 / 2000". The sample used was a solution of 10 mg of polycarbonate copolymer in 5 mL of chloroform (containing 0.05% internal standard toluene) and filtered using Millipore's "Milex LG4". The measurement was performed at 40°C and a flow rate of 0.35 mL / min. Chloroform for high performance liquid chromatography, manufactured by Wako Pure Chemical Industries, was used as the eluent.

[0077] (2)OH group equivalent The obtained polycarbonate resin was used as a measurement sample, and the JNM-AL400 (resonance frequency 400 MHz) manufactured by JEOL Ltd. was used to measure the 1 H-NMR spectra were measured, and the OH group equivalent in the polymer was calculated from the signal intensity ratio based on the structural units derived from each compound. Polymer amount: 40mg Solvent: 0.6 mL of deuterated chloroform Number of times accumulated: 256

[0078] (3) Glass transition temperature The obtained polycarbonate resin was used as a measurement sample and was measured using a thermal analysis system DSC-2910 manufactured by TA Instruments under the conditions of a nitrogen atmosphere (nitrogen flow rate: 40 ml / min) and a heating rate of 20° C. / min according to JIS K7121.

[0079] (4) Dielectric constant and dielectric tangent The obtained polycarbonate resin was dissolved in methylene chloride, and the solvent was removed from the solution to obtain a resin film. The sample was used to measure the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz using a dielectric constant meter (Anritsu Network Analyzer MS46122B, AET Cavity Resonator for 10 GHz).

[0080] (Preparation and Evaluation of Curable Resin Composition and Cured Product) 10 g of jER828 (bisphenol A type epoxy resin, epoxy equivalent 184 g / eq) manufactured by Mitsubishi Chemical Corporation as an epoxy resin and 4.6 g of the obtained polycarbonate resin were dissolved in 25 g of methyl ethyl ketone, and 8.6 g of Rikacid MH-700 manufactured by New Japan Chemical Industry Co., Ltd. as an epoxy hardener and 0.05 g of Curesol 2E4MZ manufactured by Shikoku Chemical Industry Co., Ltd. as an epoxy hardening accelerator were added to obtain a resin varnish (curable resin composition).

[0081] A glass plate with a cellophane film attached was prepared, and resin varnish was dropped onto the cellophane film and applied to a width of 200 mm using a bar coater. After coating, the coating was air-dried at room temperature for 10 minutes, and then placed in a hot air circulating oven and cured for 2 hours at 100° C. and 5 hours at 150° C. The coating was peeled off from the cellophane film to obtain a resin film (cured product). (1) Appearance The appearance (transparency) of the resulting resin varnish was evaluated visually. (2) Linear expansion coefficient A test piece of 5 mm square was cut from the resin film. The linear expansion coefficient was measured at 30°C at a heating rate of 2°C / min using a NETZSCH linear expansion coefficient measuring device "TMA4000SE." (3) Dielectric constant and dielectric tangent The resin film was used as a sample, and the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz were measured using a dielectric constant meter (Anritsu Network Analyzer MS46122B, AET Cavity Resonator for 10 GHz).

[0082] [Example 1] A reactor equipped with a thermometer, a stirrer and a reflux condenser was charged with 210 parts of 25% aqueous sodium hydroxide solution and 411 parts of ion-exchanged water, and 96 parts of 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C; denoted as BPC in the table, S-BOC manufactured by Honshu Chemical Industry Co., Ltd.) and 0.2 parts of sodium hydrosulfite (manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) were dissolved therein, and 413 parts of methylene chloride were added, and 50 parts of phosgene were blown in over about 75 minutes at 15 to 25°C while stirring. After the blowing of phosgene was completed, 210 parts of 25% aqueous sodium hydroxide solution and 8.4 parts of p-tert-butylphenol (manufactured by DIC) were added, stirring was resumed, and after emulsification, 2.6 parts of triethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) were added, and the mixture was further stirred at 26 to 33°C for 1 hour to complete the reaction.

[0083] After the reaction was completed, the product was diluted with methylene chloride and washed with water, then acidified with hydrochloric acid and washed with water. Washing with water was repeated until the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, to obtain a methylene chloride solution of polycarbonate resin. Next, this solution was passed through a filter with a mesh size of 0.3 μm, and then dropped into warm water in a kneader with an isolation chamber and a foreign matter outlet in the bearing section, and the polycarbonate resin was flaked while distilling off the methylene chloride, and the liquid-containing flakes were subsequently pulverized and dried to obtain a powder. Each property was measured, and the results are shown in Table 1.

[0084] [Example 2] A reactor equipped with a thermometer, a stirrer and a reflux condenser was charged with 209 parts of 25% aqueous sodium hydroxide solution and 242 parts of ion-exchanged water, and 11 parts of bisphenol C, 129 parts of 2,2-bis(4-hydroxy-3-tert-butylphenyl)propane (referred to as BP-OTBPA in the table, manufactured by Honshu Chemical Industry Co., Ltd.), and 0.3 parts of sodium hydrosulfite were dissolved therein, followed by adding 1073 parts of methylene chloride, 7 parts of tetrabutylammonium bromide (manufactured by Tokyo Chemical Industry Co., Ltd.), and 7.6 parts of p-tert-butylphenol, and then blowing in 50 parts of phosgene over about 75 minutes at 15 to 25° C. under stirring. After the blowing in of phosgene was completed, stirring was resumed, 2.1 parts of triethylamine was added, and the mixture was further stirred at 26 to 33° C. for 1 hour to complete the reaction.

[0085] After the reaction was completed, the product was diluted with methylene chloride and washed with water, then acidified with hydrochloric acid and washed with water. Washing with water was repeated until the conductivity of the aqueous phase was almost the same as that of ion-exchanged water, to obtain a methylene chloride solution of polycarbonate resin. Next, this solution was passed through a filter with a mesh size of 0.3 μm, and then dropped into warm water in a kneader with an isolation chamber and a foreign matter outlet in the bearing section, and the polycarbonate resin was flaked while distilling off the methylene chloride, and the liquid-containing flakes were subsequently pulverized and dried to obtain a powder. Each property was measured, and the results are shown in Table 1.

[0086] [Example 3] A polycarbonate resin powder was obtained by the same procedure as in Example 2, except that 26 parts of 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (referred to as BP-TMC in the table, manufactured by Honshu Chemical Industry Co., Ltd.) was used instead of bisphenol C, and 115 parts of 2,2-bis(4-hydroxy-3-tert-butylphenyl)propane (referred to as BP-OTBPA in the table, manufactured by Honshu Chemical Industry Co., Ltd.) was used. Each property was measured, and the results are shown in Table 1.

[0087] [Example 4] A polycarbonate resin powder was obtained by the same procedure as in Example 3, except that 5.7 parts of p-tert-butylphenol was used. Each property was measured, and the results are shown in Table 1.

[0088] [Comparative Example 1] A polycarbonate resin powder was obtained by the same procedure as in Example 1, except that 1.7 parts of p-tert-butylphenol was used. Each property was measured, and the results are shown in Table 2.

[0089] [Comparative Example 2] A polycarbonate resin powder was obtained in the same manner as in Example 3, except that 2.0 parts of p-tert-butylphenol was used. Each property was measured, and the results are shown in Table 2.

[0090] [Comparative Example 3] A polycarbonate resin powder was obtained in the same manner as in Example 1, except that 108 parts of bisphenol A (referred to as BPA in the table, manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.) was used instead of bisphenol C. Each property was measured, and the results are shown in Table 2.

[0091] [Comparative Example 4] A resin film was prepared without adding polycarbonate resin. Each property was measured, and the results are shown in Table 2.

[0092] [Table 1]

[0093] [Table 2] [Industrial Applicability]

[0094] The polycarbonate resin of the present invention exhibits a low dielectric constant, a low dielectric tangent, and excellent heat resistance. Furthermore, a curable resin composition using the polycarbonate resin as a curing agent and a cured product obtained by curing the curable resin composition exhibit a low dielectric constant, a low dielectric tangent, excellent transparency, and good dimensional stability. Therefore, the curable resin composition and the cured product are extremely useful as highly functional polymer materials, and as electrically and thermally excellent materials, they can be used in a wide range of applications, such as interlayer insulating layers for printed wiring boards, semiconductor encapsulants, electrical insulating materials, resins for copper-clad laminates, resists, encapsulating resins for electronic components, resins for liquid crystal color filters, paints, various coating agents, adhesives, build-up laminate materials, and fiber-reinforced plastic (FRP) materials.

Claims

1. A polycarbonate resin comprising a structural unit (A) represented by the following formula (1), the proportion of the structural unit (A) in all structural units being 70 mol % or more, and satisfying the following (a) and (b): (a) the weight average molecular weight of the polycarbonate resin as measured by gel permeation chromatography is in the range of 5,000 to 15,000; (b) The relative dielectric constant of polycarbonate resin at a frequency of 10 GHz measured in accordance with a cavity resonator perturbation method is in the range of 2.30 to 2.70, and the dielectric dissipation factor is in the range of 0.0001 to 0.0030. 【Chemistry 1】 (In formula (1), R 1 and R 2 each independently represents a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms; R 3 and R 4 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 6 carbon atoms, a substituted or unsubstituted cycloalkyl group having 6 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms; and X represents a single bond, a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, a substituted or unsubstituted alkylidene group having 2 to 20 carbon atoms, a substituted or unsubstituted sulfur atom, or an oxygen atom.

2. 2. The polycarbonate resin according to claim 1, wherein X in the formula (1) is at least one group selected from the group consisting of the following formula (2): 【Chemistry 2】 (R 5 and R 6 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 20 carbon atoms, and Z represents a substituted or unsubstituted alkylene group having 4 to 12 carbon atoms.

3. 2. The polycarbonate resin according to claim 1, wherein the proportion of the structural unit (A) in all structural units of the polycarbonate resin is 80 mol % or more.

4. R in the above formula (1) 1 and R 2 is at least one group selected from the group consisting of a methyl group, an isopropyl group, a tertiary butyl group, a cyclohexyl group, and a phenyl group, R 3 and R 4 The polycarbonate resin according to claim 1, wherein each of the is a hydrogen atom or a methyl group.

5. 2. The polycarbonate resin according to claim 1, which is produced by an interfacial polycondensation method between a dihydroxy compound which derives the structural unit (A) represented by the formula (1) and carbonyl chloride.

6. A curable resin composition comprising the polycarbonate resin according to any one of claims 1 to 5 and an epoxy resin.

7. The curable resin composition according to claim 6, which is a curable resin composition for forming an insulating layer of a printed wiring board.

8. A cured product obtained by curing the curable resin composition according to claim 6.

Citation Information

Patent Citations

  • Resin composition

    JP2019035056A

  • Phenol carbonate resin, method for producing the same, resin varnish, and method for producing laminated plate

    JP2019089965A

  • Allyl ether group-containing carbonate resin, method for producing the same, resin varnish, and method for manufacturing laminate

    JP2019089966A

  • Allyl group-containing carbonate resin, method for producing the same, resin varnish, and method for producing laminated plate

    JP2019089967A

  • Resin composition

    JP2022133793A